An Investigation into the Impact of School Leadership Practices and School Policies on Abu Dhabi (UAE) Governmental School Inspection Outcomes - AL THEHLI, SAMAH MOHAMED ALI (2023)
This thesis focuses on how schools implement three of six standards in the UAE inspection framework which are: Standard 3, teaching and assessment based on teaching for effective learning; Standard 5, how protection, care, guidance, and support of students has been implemented; and Standard 6, leadership, and management, which illustrates gaps in educational leadership due to differences in the direction, vision, and communication. The study’s significance is that it will help determine how school leadership practices influence governmental school inspection outcomes in the UAE. School leadership must have supporting standards that schools should implement to improve their performance. There is a gap on the impact of leadership practices on school performance management and inspection outcomes in the UAE. Although the UAE school inspection framework emphasizes a visionary education system that is knowledge-based and drives innovation through research, it provides standards to ensure comprehensive performance to achieve quality education (Ministry of Education, 2017). It clearly defines the specific governance systems that should aid schools in implementing the framework. This research is expected to provide details about new leadership practices that should be developed to help school principals identify and implement good educational and learning practices and offer recommendations on how to implement the inspection framework to improve performance. The research also provides a distinctive recommendation for school principals to develop their performance using the government excellence system in the United Arab Emirates GEM 2.